DESIJOURNAL: A VIRTUAL COMMUNITY OF THE INDIAN DIASPORA - Dhanik Sulistyarini (Universitas Padjadjaran, 2008)
This essay discusses the role of the Internet for Indian diasporic community. I argue that the internet is a powerful medium in maintaining their sense of identity as Indians. I use an Indian online magazine, Desijournal (available at www.desijournal.com), as a case study to support my argument. Various issues are discussed in this essay, such as the concepts of diasporic and virtual communities, and the sense of identity among them. Keywords: internet, diaspora, cultural identity, virtual community